IEEE CIS Philippines Chapter report - Dadios, Elmer P. (Animo Repository, 2012)
The IEEE Computational Intelligence Society (CIS) Philippines Chapter organized the first part of the IEEE CIS Philippines Chapter Distinguished Lecture Series on November 4, 2011, Manila. During the event, various members of the IEEE CIS Philippines Chapter presented their research work. Engr. Ryan Rhay Vicerra presented 'Robot path planning simulator using genetic algorithm', Engr. Alejandro Ballado presented '6-element high-gain Yagi-Uda antenna design for RFID tag using genetic algorithm', and Engr. Erwin Daculan, 'Optimization of test functions using simple genetic algorithm'. The second part of the lecture series was held on December 14, 2011, that included lecture given by Dr. Gary Yen of Oklahoma State University on 'Cultural- based particle swarm optimization for multi-objective optimization and performance metrics ensemble'. Dr. Gary Yen also introduced IEEE CIS, its history, mission and activities during the seminar.